Effects of Xiao Chengqi Formula on Slow Transit Constipation by Assessing Gut Microbiota and Metabolomics Analysis in vitro and in vivo - Qian Zhou; Qian Zhou; Qian Zhou; Di Zhang; Di Zhang; Di Zhang; Heng Zhang; Heng Zhang; Heng Zhang; Xingyang Wan; Xingyang Wan; Xingyang Wan; et al. (Frontiers Media S.A., 2022)
The Xiao Chengqi (XCQ) formula is a newly constituted traditional Chinese medicine prescription in the treatment of intestinal motility deficiency and is effective in patients with slow transit constipation (STC). XCQ formula was reconstructed based on a "Chengqi" decoction. Astragali Radix, Angelicae Sinensis Radix, and cooked ground Salviae Miltiorrhizae Radix et Rhizoma were added to the prescription to enhance. An STC rat model was constructed and treated with the formula to understand the detailed mechanism by which XCQ promotes intestinal peristalsis. The effects of the XCQ formula on intestinal microflora and metabolic levels and the possible molecular mechanism of its regulation were explored using 16S rDNA sequencing, metabolomics sequencing, and tissue RNA sequencing. The results showed a significant decrease in the abundance of Roseburia spp. in the feces of STC rats, a significant decrease in the content of butyl aminobenzene (BAB) in feces, and an increase in the number of interstitial cells of Cajal (ICC) in the colon of STC rats. Furthermore, in vitro and in vivo experiments revealed that BAB could activate IL-21R on the ICC surface, upregulate the phosphorylation of the downstream molecules STAT3 and ERK, and inhibit loperamide-induced ICC apoptosis. Therefore, the XCQ formula can improve the defecation status of patients with STC by protecting ICC activity, promoting the colonization of Roseburia spp. to promote peristalsis, and increasing the BAB content after metabolism.